Pemanfaatan Beberapa Kaldu Hewan sebagai Bahan Formula Cair Pseudomonas fluorescens P60 untuk Mengendalikan Sclerotium rolfsii pada Tanaman Mentimun - Loekas Soesanto; Endang Mugiastuti; Ruth Feti Rahayuniati (Universitas Gadjah Mada, 2011)
A research aiming at knowing the potency of several animal broths as organic liquid formula of Pseudomonas fluorescens P60, soaking period of Sclerotium rolfsii sclerotia, and its application method on cucumber stem-end rot was done. Completely randomized design and randomized block design both arranged by factorial were used for in vitro and in planta tests, respectively. The first factor was six kinds of animal broth, i.e., golden snail, local chicken,broiler chicken, catfish, cow bone, and rat. The second one for in vitro test was the soaking period in the Pseudomonas fluorescens P60 formula, i.e., 0, 1, 10, and 100 hours and for in planta one was application methods, i.e., seed soaking or crop spraying. Result of the research showed that the best animal broth as liquid formula for Pseudomonas fluorescens P60 was golden snail broth indicated by suppression of sclerotial germination up to 97.4% after soaking for 100 hours. The best application method to suppress the disease was spraying method showed by suppressed of sclerotial germination, longer incubation period, and suppressed disease incidence and sclerotial late population of 55.79, 147.35, 66.67, and 59.68%, repectively. Spraying the formula could also increase crop height difference, fresh and dry weight of crop, fresh and dry weight of root, and root length to 146.83, 86.62, 112.5, 87.88, 140, and 159.68%, respectively.